THE SINGLE SPINE PAY POLICY: CAN IGNORANCE DERAIL THE BENEFITS IT HAS ON THE GHANAIAN PUBLIC SERVICE WORKER? - Joseph Attiah Seniwoliba (European Scientific Journal, ESJ, 2014)
A better paid public sector could be more efficient in the delivery of important services of interest to the business community no matter the sector of business involved. The public sector is the main engine of growth for most developing countries. It therefore performs many important tasks that starts business and keep them in operation. The study therefore seeks to enlighten Executives of Ghanaian Labour Unions (GLU) on dispute resolution procedures for negotiation as enshrined in the Labour Act 2003 (Act 651), the rationale for the introduction of the single spine pay policy, find out about the perceived inequalities in the new pay policy and to assess the effects of the SSPP on the Ghanaian economy. The study collected data from executives of labour unions such as Federation of University Senior Staff Association of Ghana (FUSSAG), Teachers and Educational Workers Union (TEWU), University Teachers Association of Ghana (UTAG) and Civil and Local Government Staff Association of Ghana (CLOGSAG) using structured interviews. A personal administered questionnaire was also used to seek views from some TEWU and FUSSAG executives at the University for Development Studies (UDS) at its Tamale Campus and finally a review of the Government’s White Paper (GWP) on the SSSS. One major finding was that, it is clearly stated in the Government’s White Paper that, “no worker should be worst of than they are in the prevailing system”. With this statement, workers had great expectations that significant salary increases should and will be accessible to everyone irrespective of merit but that was not the case hence, the current strike actions in the public sector. The research however, challenged Government to define her labour laws very well and stop remunerating agitating workers during strikes. This will stop unions from continuing to be free riders on the ignorance of Government. If it is made clear to labour unions’ that their responsibilities during industrial actions are not to be borne by the tax payer, then labour unions will seize to organize strikes as their best tool for meeting their demands. The constant strike actions are both dangerous and costly to the development, stability and economic productivity of Ghana. In such instances, the poor tax payer pays the price in exponential rates.